On the relationship between regional trade agreements and agricultural technology and productivity - Pascal L. Ghazalian (Agricultural and Food Economics, 2013)
The implementation of a Regional Trade Agreement (RTA) is normally accompanied with a rise in market competition levels, in domestic agricultural markets through increases in imports and in foreign agricultural markets through increases in exports. These effects are expected to induce adjustments in agricultural technology and productivity in the importing and exporting countries. This paper analyzes the implications of these adjustments in the context of Viner's (The Customs Union Issue. Carnegie Endowment for International Peace: New York, NY, 1950) conventional partial equilibrium framework with perfectly elastic foreign supply schedules faced by the importing member country. It also examines these implications in the context of Pomfret's (Review of World Economics, 122(3): 439-465, 1986) extended partial equilibrium framework depicting upward-sloping foreign supply schedules for the importing member country. The analysis underscores important changes and redistributions through the RTA's initial benefits and losses, following the RTA-induced adjustments in agricultural technology and productivity. Some analytical considerations are also discussed in the context of vertical agricultural markets. Finally, an empirical investigation is carried out, revealing different implications of membership in the European Union (EU) and its predecessor, the European Economic Community (EEC), for productivity in the agricultural sector.
Keywords: 330